PENYEBARAN PAHAM INGKAR SUNNAH MODERN: Motivasi, Tokoh, dan Sanggahan Terhadapnya - Febriansyah Martono (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
Ingkar sunnah is a thought that rejects the legitimacy of hadith as the second source of Islamic teachings after the Koran. In its journey, this thought is not new in the modern era. This practice of understanding undermines the purity of the Islamic religion through its source, in this case the hadith of the Prophet. There are three categories in this understanding, namely, 1) rejecting the entire hadith and only accepting the Koran, 2) rejecting hadith except those that are mutawatir, 3) rejecting hadiths that are inconsistent according to logic and science. This study aims to provide a description of the characteristics of modern sunnah denial. It was found that the difference between modern and classical denial of sunnah is one of the reasons that modern denial of sunnah has become institutionalized and massive.